2012
DOI: 10.1111/eje.12006
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of educational strategies in postgraduate dental education using student and graduate feedback: findings from a qualitative study in New Zealand

Abstract: Introduction: Research suggests that students' perceptions should be considered in any discussion of their education. However, to date, there has been no systematic examination of New Zealand postgraduate dental students' learning processes in both the research and clinical settings. This study aimed to obtain in-depth qualitative insights into student and graduate perspectives of effective and ineffective learning experiences during their postgraduate dental education.Methods: Data were collected in 2010 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…The findings reported in this article are a part of a larger project from which some findings have previously been published . The overall aim of the larger project was to explore the characteristics of effective and ineffective learning experiences in clinical, didactic and research settings, as identified by the 2010 final‐year DClinDent students and the first cohort of DClinDent graduates (completed in 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings reported in this article are a part of a larger project from which some findings have previously been published . The overall aim of the larger project was to explore the characteristics of effective and ineffective learning experiences in clinical, didactic and research settings, as identified by the 2010 final‐year DClinDent students and the first cohort of DClinDent graduates (completed in 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The major themes included supervisory approaches, characteristics of the learning process and characteristics of the physical learning environment. Research findings related to supervisory approaches and specific parts of learning processes have been previously published. Those two published papers had distinctively different content, focus, scope and findings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggest that students' perceptions should be considered in any discussion of their education. 1,2 The consensus opinion in the dental education literature is that teacher's and student's feedback on their learning experiences should inform all discussion and decisions relating to the education. [3][4][5][6] Researchers interested in eliciting students' feedback emphasize that attention to "student's voice" is important because they have distinctive perspectives of teaching and learning, which can offer in-depth information.…”
Section: Introductionmentioning
confidence: 99%